Ridge and socket preservation management for prevention of bone resorption as a preparation for the placement of implant and denture : Penatalaksanaan ridge dan socket preservation untuk pencegahan resorbsi tulang sebagai persiapan pemasangan gigi tiruan dan implan - Arni Irawaty Djais; Firman salam; Eri Hendra Jubhari; Shinta Rahma; Rachmi Bachtiar (Makassar Dental Journal PDGI Makassar, 2021)
Alveolar ridges usually undergo a change in shape and height due to tooth loss. This can make it difficult to install dentures or implants. Preservation of the socket post tooth extraction can maintain the height and width of the alveolar ridge. Preservation of ridges and socketscan be done with atraumatic extraction, the use of bone graft or membrane, and a combination of bone graft and membrane.